DISPUTE SETTLEMENT IN ANTROPOLOGI OF LAW PERSPECTIVE - Taryono Taryono (Surakarta Law and Society Journal, 2018)
In the perspective of anthropology of law, disputes are social phenomena that are inseparable from human life, especially in multicultural society. He cannot be avoided or neglected in common life. What must be done is how the conflict is managed, controlled, accommodated, and resolved peacefully and wisely so as not to cause social disintegration in people's lives. In anthropology of law, the dispute and its settlement are one of the points that get a lot of attention. This focus of attention is the focus of anthropology of law in relation to the perception that the law operating actually appears in the process of dispute, in the settlement process taken, and in matters that occur after the decision is handed down by mediators or by parties negotiating, or by neutral third party. In the perspective of anthropology of law, the settlement of disputes can be done in two ways, namely first, the settlement of disputes through non-legal institutions; and second, settlement of disputes through legal institutions. The selection of dispute resolution through legal institutions and non-legal institutions tends to be determined by the community itself. In a simple or traditional society whose legal system has not developed tends to resolve the dispute with non-legal institutions. Whereas for modern and advanced society whose legal system has developed and the problems faced increasingly complex tend to resolve the dispute to legal institutions. Keywords: Dispute resolution, anthropology of law, settlement of litigation disputes, non legal dispute resolution